Response surface modeling of low-cost pneumatic nursery protray seeder parameters for tomato (Solanum lycopersicum) seedlings (Current Horticulture, 2024)
The performance of the developed pneumatic nursery protray seeder was evaluated in terms of miss seeding, single seeding,  multiple seeding, seeding efficiency, and seeder output in the laboratory for different levels of mouthpiece diameter and suction  pressure. With a mouthpiece diameter of 0.84 mm and suction pressure of 6.2 kPa, it was found that 59.25% of single seeding,  97.69% seeding efficiency, and a seeder output of 67 cells/min were suitable for tomato seedlings. The pneumatic protray seeder  resulted in a saving of ₹15.04 per 1000 cells sown compared to manual seeding. The payback period was 104.7 hours (3.58% of  the expected life of the pneumatic protray seeder).
Keywords: Mouthpiece diameter; Nursery protray seeder; Optimization; Suction pressure; Suction unit; Seedlings